A Comparison of Lower Dental Arch Changes Using Two Types of Space Regainers: A Removable Appliance with a Distalizing Screw and a Fixed Double-Banded Appliance. (16th April 2022) - Enteghad, Shabnam; Golfeshan, Farzaneh; Sardarian, Ahmadreza; Navaei, Hooman
Abstract : Aim . The aim of this study was to compare lower dental arch changes using two types of space regainers, including a removable appliance with a distalizing screw and a fixed double-banded appliance. Methods and Materials . In this case-control study, the study sample was comprised of thirty-eight children with mixed dentitions, all of whom had unilateral space deficiency due to premature loss of the second deciduous molar in the mandibular arch. Patients were treated with either a removable appliance with a distalizing screw or a fixed double-banded space regainer (DBSR) ( n  = 19). Pre- and posttreatment dental casts and lateral cephalograms of patients were evaluated to compare the effects of the two space-regaining devices on the mandibular dental arch. The data were analyzed using paired and independent t -tests. Results . Available space, molar angle, IMPA, and the first molar distance to the mandibular plane and symphysis increased significantly in both groups (P < 0.001 ). The mean amount of IMPA changes was significantly greater in the distalizing screw group than in the DBSR group (P < 0.05 ). But, there were no statistically significant differences between the mean changes of available space, molar angle, and the first molar distance to the mandibular plane and symphysis in the distalizing screw and the DBSR group (P < 0.05 ). The DBSR group's treatment time was significantly shorter (P < 0.001 ). Conclusion . The removable device with a distalizing screw and the DBSR were both able to regain mild-to-moderate unilateral space loss, achieving an increase in molar angle, IMPA, and molar extrusion. However, treatment time with the DBSR was shorter and with less incisor tipping as a side effect.